if 2x/5 – 2 = 5 – 3x/5 , then x = (step-by-step explanation) {urgent pls dont reject} mark is 59

Question

if 2x/5 – 2 = 5 – 3x/5 , then x = (step-by-step explanation) {urgent pls dont reject} mark is 59

in progress 0
Madelyn 4 weeks 2021-08-17T14:48:39+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-17T14:50:03+00:00
    • 2x/5 – 2 = 5 – 3x/5


    • =2x/5 +3x/5 =5+2


    • =5x/5=7


    • =5x=35


    • =x=35/5


    x=7

    0
    2021-08-17T14:50:37+00:00

     \huge\bf\red{AnswEr:-}

    \bigstarTo do this with 2x+5=3x, you first need to remove the x’s from whichever side is easiest to do so. In this case, it’s easiest to remove the 2x and the question is even kind enough to be solved in that one step!

    I’ll write out what needs to be done with brackets to keep it easy to understand

    (2x + 5) – 2x = 5

    (3x) – 2x = 1x (x)

    Therefore:

    5 = x or more nicely written: x=5

    \bigstarHope this explains it!

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )